SISTEM BAGI HASIL DALAM PERBANKAN SYARI’AH (Aspek Teologis, Syari’ah dan Karakteristik Operasional Keuangan) - Iswanto, Bambang (IAIN Samarinda, 2012)
Shari'a banking and conventional banking as financial institutions have many similarities in the quest for profit, but there are some fundamental differences between the two. This paper seeks to review the system of revenue sharing in Shariah banking operations are focused on the study of theology, shari'a finance and operational characteristics that made the difference between shari'a banking with conventional banking.